Altered levels of sphingolipid metabolites in serum of locally advanced rectal cancer patients: a pilot study - Bjelanovic, Jasna; Nikolić, Aleksandra; Aslan, Mutay; Miladinov, Marko; Kotur, Nikola; Barišić, Goran; Dragićević, Sandra (Journal of Medical Biochemistry, 2025)
ABSTRACT Background: Altered sphingolipid levels might contribute to rectal cancer development, progression and therapy response by regulating various biological processes, including apoptosis. This study aimed to analyse the serum sphingolipid profile in rectal cancer patients and investigate its association with the apoptotic status of tumour tissue and therapy response. Methods: Ceramide (CER) and sphingomyelin (SM) serum levels were analysed in 22 patients with locally advanced rectal cancer and 24 healthy individuals by ultrafast liquid chromatography coupled with tandem mass spectrometry. The expression of pro-apoptotic BAX (BCL2 associated X, apoptosis regulator) and anti-apoptotic BCL2 (BCL2 apoptosis regulator) was analysed in tumour and corresponding healthy tissue samples of patients by quantitative real-time PCR. Results: Significantly lower serum levels of C18 CER, C22 CER, C24 CER, C18 SM and C24 SM were observed in patients than in controls (P<0.05). For C20 CER, C22 CER and C24 CER, a positive correlation with the pro-apoptotic status of tumour tissue was found (r=0.619, P=0.018; r=0.694, P=0.006 and r=0.601, P=0.023, respectively). No difference in serum sphingolipid levels was found between patients with good, moderate, and poor responses to therapy. Conclusions: These results support the involvement of sphingolipids in rectal cancer. However, further studies, including a larger cohort of subjects, are needed to clarify the association of sphingolipid metabolites with therapy response. Keywords: apoptosis, neoadjuvant chemoradiotherapy, rectal cancer, sphingolipids